Neurological Manifestations of HIV-AIDS at Tertiary Care Hospital Quetta - Panezai, Shahrukh; Muhammad Shoaib; Khoso, Noor Ahmed; Panezai, Mahrukh; Essa, Syed Muhammad; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2024)
Background: HIV and AIDS continue to pose substantial global health challenges, particularly in resource-constrained settings like Pakistan. This study investigated the prevalence and types of neurological manifestations among HIV-AIDS patients treated at a tertiary care hospital in Quetta. Methodology: A cross-sectional analysis was conducted on 200 HIV-AIDS patients using questionnaires, medical records, and laboratory findings. Results: Neurological manifestations were observed in 70% of the patients, with peripheral neuropathy (40%) being the most common condition, followed by HIV-associated neurocognitive disorders (30%), progressive multifocal leukoencephalopathy (10%), cryptococcal meningitis (7.5%), and cerebral toxoplasmosis (5%). Key risk factors included low CD4 counts (